Genetic Parameter Estimation of Teak Clonal Test At 5 Years Old in Wonogiri, Central Java - Hamdan, Hamdan Adma Adinugraha; Mahfudz, Mahfudz (Jurnal Wasian, 2016)
Trial research of teak clones was located in Wonogiri, Central Java. This research was conducted in order to evaluate the growth performance of teak clones that can be developed for forest plantation and private forest. Establishment of teak clones test was conducted in 2002 using 20 clones with Randomized Completely Block Design/RCBD consisting of 5 ramets and 5 replications with plant spacing of 2 m x 6 m . The second plot was established in 2005 using 100 clones with RCBD that consisted of 3 ramets and 5 replications with spacing of 2 m x 6 m. The observation and measurement on height and diameter at breast height/dbh were carried out periodically in every year to determine the level of plant growth The results showed that the average growth at the age of 5 years in two test plot clones are height from 8,73 to 9,97 m , tree diameter from 8.61 to 13.14 cm and tree volume estimated 0,046 - 0,103 m3. Estimated heritability clones of tree height and diameter were 0,18; 0,29 in plot 1 and 0,32; 0,38 in plot 2.